3RD Crossing the Palaeontological - Ecological Gap – Vilnius, 28th-31st August 2023 - Spiridonov, Andrej; Budrys, Eduardas; Dankina, Darja; Rinkevičiūtė, Simona (Vilnius University Proceedings, 2023)
-